SUNSCREEN ACTIVITY OF SUGAR PALM (ARENGA PINNATA (WURMB) MERR.) LEAF STALK ASHES EXTRACT - Esti Rachmawati Sadiyah (Jurnal Ilmiah Farmasi Farmasyifa, 2019)
Sugar palm leaf stalk (petioles) ashes traditionally used as a daily cosmetic by Sundanese women to keep their skin smooth. Sugar palm leaf stalk ashes also used to treat acne, smallpox, and burns. The study was aimed to test the sunscreen activity of ashes extracts from sugar palm leaf stalk. The ashes were extracted using soxhlet and 96% ethanol as solvent. The sunscreen activity test was performed on the extract using UV-Vis spectrophotometer. Determination of Sun Protection Factor (SPF) value was done at 290-320 nm (UV-B wavelength) with 5 nm interval. The ashes extract of sugar palm leaf stalk showed the effectiveness of sunscreen activity at 10,000 ppm (SPF value = 9) as maximum protection. The SPF value was determined using Mansur mathematical equation. The determination of pigmentation transmittant was done at 322.5 – 372.5 nm, with 2.5 nm interval. Based on the result of pigmentation transmittance percentages, the sunscreen profile of sugar palm leaf stalk ashes extract (2000-10.000 ppm) showed the category of extra protection up to sunblock, according to classification from Balsam & Sagarin (1972). To be concluded, the ashes extract of sugar palm leaf stalk was a potential sunscreen. Further in vivo analysis should be done to confirm this potency.